Gandhi's conscience keeper - "Srinivasan, Vasanthi" (Ranikhet, 2009)
Hailed by Mahatma Gandhi as his conscience keeper, Chakravarti Rajagopalachari (1878 1972; better known as Rajaji) epitomized the practical wisdom, religious tolerance, and statesmanship that Gandhi brought to the nationalist movement. He articulated how Gandhi s ideas and practices could be reconciled with the needs and aspirations of a modern nation-state. His political and philosophical positions were argued in a manner, and with an ideological orientation, strikingly different from that of Jawaharlal Nehru. And yet Rajaji remains virtually unknown today. Vasanthi Srinivasan presents Rajaji s vision as that of a theocentric liberal. She argues that he tried to temper majoritarian democracy with statesmanship, a free economy with civic virtue, realistic patriotism with genuine internationalism, and secularism with a religiosity derived from the Hindu epics. Examining his political ideas and actions alongside his literary works, as well as in relation to statesmen-ideologues such as Nehru and Periyar, she shows how Rajaji steered clear of ideological dogma and charted an ethic of responsibility.
Keywords: C. Rajagopalachari-Political ideas